Drug control of biofilm dispersion due to regulation of the activity of bacterial cyclic guanosine monophosphate (part 2) - А.Е. Abaturov (Zaslavsky O.Yu., 2020)
The infectious process caused by pathogenic bacteria can be accompanied by the formation of a biofilm, which determines the safety of bacteria and a decrease in the effectiveness of antibacterial agents. The development of drugs that contribute to the dispersion of bacterial biofilms is one of the most important therapeutic areas that contribute to solving the problem of treating bacterial infections caused by microorganisms that are resistant to antibacterial agents. One of the target bacterial molecules involved in biofilm formation, which can be subjected to drug regulation, is a secondary messenger nucleoside molecule - cyclic dinucleotide GMP (c-di-GMP). Drug suppression of the level of intra-bacterial concentration of the messenger molecule of c-di-GMP or blocking its activity helps prevent the formation and causes the destruction of the bacterial biofilm, which is accompanied by an increase in the level of effectiveness of treatment of bacterial infections. A decrease in the level of intra-bacterial concentration of c-di-GMP can be achieved by inhibiting the synthesis processes due to: 1) suppression of diguanylate cyclase activity; 2) restrictions on the availability of substrates required for the synthesis of c-di-GMP; 3) increased degradation of the c-di-GMP molecule due to activation of phosphodiesterase activity. The treatment of infectious diseases, which are accompanied by the formation of biofilms, requires the medical induction of the dispersion of bacteria from biofilms and the use of targeted antibiotic drugs that cause the death of bacteria released from biofilms. The use of analogues of c-di-GMP, which disrupt the functioning of native c-di-GMP, and the blocking of targeted receptors and other molecular structures can also lead to dispersion of the bacterial biofilm. Medicines that modulate the activity of c-di-GMP will increase the effectiveness of the treatment of bacterial infections, which are accompanied by the formation of biofilms.